LIVER TRANSPLANTATION FROM SEXAGENARIAN AND OLDER - S. V. Gautier; М. N. Kornilov; I. A. Miloserdov; M. G. Minina; D. N. Kruglov; S. I. Zubenko (Вестник трансплантологии и искусственных органов, 2018)
Donor organs shortage leads to extending criteria for deceased liver donation in the whole world.Aim: to compare results of deceased donor liver transplantation (DDLT) depending of donor age over 60 years old.Materials and methods: the study includes 390 DDLT from January 2010 to November 2017. All liver donors separated by age for two groups: I – 60 years and older (n = 26); II – younger than 60 years (n = 364). All donors were standardized by demographic, laboratory fi ndings and inotropic drug requirement. Results: no difference between both groups in severity of ischemia-reperfusion injury, ICU or in-hospital staying (median 2 and 7,5 days respectively) was found. There is also no difference between biliary or vascular complication rate. 5-year actuarial survival rate found no difference between both groups (I: 70%: II: 76%, p = 0,54).Conclusion. Using grafts from donors older than 60 years don’t worsen early and late results of DDLT. Care should be taken to avoid other risk factors (cold ischemia time, warm ischemia time).